Molecular study of colorectal carcinoma and EGFR gene mutations: EGFR gene mutations and colorectal carcinoma - Rasheed Abubakir, Shayan; Hidayat, Hazha Jamal (Cellular and Molecular Biology, 2023)
The development of various human tumors can be related to the activation of the Epidermal growth factor receptor (EGFR) and its subsequent signaling pathways. There are so much alertness and awareness that has been given to the EGFR pathway recently because EGFR and some downstream components together render as targets for anticancer therapy. The EGFR pathway and its impact on colorectal carcinogenesis and assessments are the assertiveness in this paper. In this study, we took 1034 patients with colorectal carcinoma that were recorded as a medical survey we used a standard questionnaire for those patients and we used real time PCR for 30 patients from 134 cases that have colorectal carcinoma to detect if there is any mutation in the EGFR gene. We chose 4 exons for that purpose which were exons (18),(19),(20) and (21) of the EGFR gene. After deparaffinization and DNA extraction from the tissues of patients with colorectal carcinoma, we used real-time PCR technique by using (Rotor gene) kit and we were run our samples with the control group of the same patients and internal control from the kit to compare if there was any mutation but there was not any mutation in those exons of our (30) samples of paraffin-embedded (FFPE) tissues.